YOUTH, VIOLENCE AND EDUCATION: NARRATIVES OF THE SOCIO-EDUCATIONAL SYSTEM - dos Reis, Laura de Souza Alves; Dantas , Alice Vitória de Miranda; Faceira, Lobelia da Silva (Seven Editora, 2024)
This article aims to reflect on socio-educational measures in the state of Rio de Janeiro, through the analysis of the documentary "Juízo" (2022), directed by Maria Augusta Ramos and produced by Diler Trindade, in conjunction with the study of the Statute of the Child and Adolescent (ECA/ Law No. 8.069/1990). The work was produced by students with scientific initiation scholarships and academic incentive scholarship holders, linked to the research entitled "Social policies and Prison: an evaluation of the penal execution policy", developed by the Graduate Program in Social Memory and the School of Social Work of the Federal University of the state of Rio de Janeiro. The research was carried out through literature review and analysis of legal documents: law n° 8.069 (Statute of the Child and Adolescent), decree n° 17.943-A (Melo Mattos Code), law n° 6.697 (Minors Code), decree n° 847 (Penal Code of 1890) and law n° 12.594 (National System of Socio-educational Assistance). The article highlights the importance of problematizing the possibilities around the elaboration and execution of socio-educational measures by means other than punitive and individualizing, as well as the realization of critical analyses of the neoliberal context within capitalist society and the various expressions of violence, intersecting the markers of class, race and gender. DOI:https://doi.org/10.56238/sevened2024.037-034